The CLARIN infrastructure as an interoperable language technology platform for SSH and beyond. - Branco, A.; Eskevich, M.; Frontini, F.; Hajič, J.; Hinrichs, E.; Jong, F. de; Kamocki, P.; König, A.; Lindén, K.; Navarretta, C.; Piasecki, M.; Piperidis, S.; et al. (Language Resources & Evaluation, 2025)
CLARIN is a European Research Infrastructure Consortium developing and providing a federated and interoperable platform to support scientists in the field of the Social Sciences and Humanities in carrying-out language-related research. This contribution provides an overview of the entire infrastructure with a particular focus on tool interoperability, ease of access to research data, tools and services, the importance of sharing knowledge within and across (national) communities, and community building. By taking into account FAIR principles from the very beginning, CLARIN succeeded in becoming a successful example of a research infrastructure that is actively used by its members. The benefits CLARIN members reap from their infrastructure secure a future for their common good that is both sustainable and attractive to partners beyond the original target groups.